Identifying patterns and affordances in location-based games: The practices of Niantic - Silva, Bruno C. da; Freitas, Lucas M.; Maia, José G. R.; Viana, Windson (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento Digital, 2024)
Niantic is a global company pioneering in the immersive gaming industry, with this feature driven by location-based game mechanics. This paper identifies and analyzes affordances and game patterns related to players' locations in Niantic's games—Peridot, Monster Hunter Now, Pikmin Bloom, Pokémon GO, and Ingress—to uncover LBG patterns and perceived affordances. The analysis shows that Search-and-Find and Change-of-Distance are the most stimulated mechanics. The impact of these game dynamics necessitates careful implementation in urban environments for healthy and safe gameplay. Affordances in LBGs frequently use real-world locations, and procedural content generation could enhance user experiences without location-based distortions.